My friend likes this brand: Do ads with social context attract more attention on social networking sites?. (July 2018) - Windels, Kasey; Heo, Jun; Jeong, Yongick; Porter, Lance; Jung, A-Reum; Wang, Rui
Abstract: This study examined differences between native advertisements with and without friend referrals on social networking sites. Specifically, we examined whether native ads that included friend referrals attracted more attention than native advertisements that did not include friend referrals. Further, the study examined whether participants with higher privacy concerns reacted differently to friend referrals than did individuals with lower privacy concerns. Results suggested that participants had longer attention duration for ads without friend referrals, especially among individuals with high privacy concerns. This suggests a popular form of advertising on social media, those thought to be effective due to the social context of a friend referral, often underperforms when compared to ads that don't include friend referrals. Highlights: Some SNS native ads include the social context cue of friend referrals. Native ads without (vs. with) friend referrals attract more attention. Users with high privacy concerns avoid ads with friend referrals. Users with low privacy concerns quickly discover ads with friend referrals.